Pengelolaan Limbah Kotoran Hewan Menjadi Pupuk Organik dan Optimalisasi Pemasaran Menggunakan Media Digital pada Peternakan Kambing di Tengah Kota Semarang - Yusuf Wahyu Setiya Putra; Kanafi Kanafi; Mira Fitriana (Institut Teknologi dan Bisnis Semarang, 2023)
The service that will be carried out is to answer the problem of an active goat farm called Ciliwung Farm which is in the middle of Semarang City, precisely in the Citarum area, East Semarang District. Besides being in the middle of the city, this farm has a number of goats and sheep of approximately 80 heads. It is feared that the location of the farm which is really in the middle of a settlement will create disturbances for the people who are in the vicinity. There is also quite a lot of livestock manure produced, around 40kg - 80kg per day, where the manure is not processed at all by breeders and is only sold to goat manure collectors at very cheap prices, namely Rp. 500 - Rp. 2,000 per kilogram. Then the purpose of this service is to make a goat manure management system from the beginning until it can finally become organic fertilizer that has economic value. Starting from making tools and materials to process goat manure into organic fertilizer, making packaging or packaging from organic fertilizer (including tools and materials for making packaging), to the process of marketing organic fertilizer using digital media as a media for promotion and sales. So that Ciliwung Farm can process its own livestock manure into organic fertilizer and can market its own organic fertilizer. The results of this service apart from the animal manure processing equipment and digital media as a marketing medium are publishing devotional journals in national journals with ISSN, involving articles in electronic media and video content of community service activities